Analisis Value Stream Mapping dan Eco-Efficiency Untuk Meminimasi Waste dan Dampak Negatif Terhadap Lingkungan Proses Produksi Kayu Lapis - Ian Derry (Universitas Mercu Buana, 2022)
PT. Sumber Graha Sejahtera (Sampoerna Kayoe) is a company that produces plywood products. In identification, the company still produces waste in its production process. Therefore, efforts are needed to minimize waste in order to make the process more efficient and identify whether the process is environmentally friendly with consideration of the level of eco efficiency. This research includes steps, among others, by analyzing the value stream mapping to find out activities that have value added and are categorized as NVA. Furthermore, environmental impact measurement is carried out using LCA (Life Cycle Analysis). In the plywood production process, the waste that often occurs is the presence of bubbles in the plywood. From the measurement results for 1 piece of plywood, the Life Cycle Impact Assessment Damage Category Human Health is 0.00246 DAILY, Damage Category Ecosystem Quality is 0.0135 PDF*m2yr and for Damage Category Resources is 0.0008 MJ surplus. The eco cost is IDR 1,266,196.44. The proposed process to minimize waste is to combine the grading process and the final packaging process so that there is no waiting lag from the grading process to the final packaging process.